2018
DOI: 10.24136/atest.2018.378
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated food transport in Poland

Abstract: The article discusses the most important information related to the transport of refrigerated cargo. The survey has been carried out among producers and distributors of chilled foods. The aim of the research was to present transport companies, used ways of transport, as well as means of transport during the delivery of food products. The research was carried out using a questionnaire ad-dressed to companies organizing such transport. The companies taking part in the survey are small and medium-sized, mainly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These damages may have different consequences, starting with a simple package deformation that leads to rejection by the recipient or to a decreased attractive-ness to consumers [32]. Palka [12] showed that the most frequent transport damage found in Polish companies was mechanical damage. It was the most common indicated threat and occurred in nearly 75% of respondents.…”
Section: Verification Identified Rp On the Basis Of A Surveymentioning
confidence: 99%
“…These damages may have different consequences, starting with a simple package deformation that leads to rejection by the recipient or to a decreased attractive-ness to consumers [32]. Palka [12] showed that the most frequent transport damage found in Polish companies was mechanical damage. It was the most common indicated threat and occurred in nearly 75% of respondents.…”
Section: Verification Identified Rp On the Basis Of A Surveymentioning
confidence: 99%